Comparative Studies Of The Effects Of Microstructures On The Corrosion Behavior Of Micro-Alloyed Steels In Unbuffered 3.5 Wt% Nacl Saturated With Co2 - Onyeji, Lawrence I.; Girish M. Kale; M. Bijan Kermani (Zenodo, 2017)
Corrosion problem which exists in every stage of oil and gas production has been a great challenge to the operators in the industry. The conventional carbon steel with all its inherent advantages has been adjudged susceptible to the aggressive corrosion environment of oilfield. This has aroused increased interest in the use of micro alloyed steels for oil and gas production and transportation. The corrosion behavior of three commercially supplied micro alloyed steels designated as A, B, and C have been investigated with API 5L X65 as reference samples. Electrochemical corrosion tests were conducted in an unbuffered 3.5 wt% NaCl solution saturated with CO 2 at 30 0 C for 24 hours. Pre-corrosion analyses revealed that samples A, B and X65 consist of ferrite-pearlite microstructures but with different grain sizes, shapes and distribution whereas sample C has bainitic microstructure with dispersed acicular ferrites. The results of the electrochemical corrosion tests showed that within the experimental conditions, the corrosion rate of the samples can be ranked as CR (A) < CR (X65) < CR (B) < CR (C) . These results are attributed to difference in microstructures of the samples as depicted by ASTM grain size number in accordance with ASTM E112-12 Standard and ferrite-pearlite volume fractions determined by ImageJ Fiji grain size analysis software. : {"references": ["Ilman, M., Analysis of internal corrosion in subsea oil pipeline. Case Studies in Engineering Failure Analysis, 2014. 2(1): p. 1-8.", "Su\u00e1rez Bermejo, J.C. and M.A. Herreros Sierra, New fiber-metal hybrid laminated material, MALECON. 2008.", "Dugstad, A. Fundamental aspects of CO2 metal loss corrosion-part 1: mechanism in CORROSION 2006. 2006. NACE International.", "Edmonds, D.V. and R.C. Cochrane, The effect of alloying on the resistance of carbon steel for oilfield applications to CO2 corrosion. Materials Research, 2005. 8(4): p. 377-385.", "Edelugo, S., The timed response of different types of GRP laminates on exposure to various strengths of alkaline and acidic environments. Journal of advanced materials, 2009. 41(2): p. 79-87.", "El-Lateef, H.A., et al., Corrosion protection of steel pipelines against CO2 corrosion\u2014a review. Chem. J, 2012. 2(2): p. 52-63.", "Kermani, B., et al. Development of low carbon Cr-Mo steels with exceptional corrosion resistance for oilfield applications. in CORROSION 2001. 2001. NACE International.", "Kermani, M. and A. Morshed, Carbon dioxide corrosion in oil and gas production-A compendium. Corrosion, 2003. 59(8): p. 659-683.", "Davis, J.R., Alloying: understanding the basics. 2001: ASM international.\n[10]\tPopoola, L.T., et al., Corrosion problems during oil and gas production and its mitigation. International Journal of Industrial Chemistry, 2013. 4(1): p. 1-15.\n[11]\tLopez, D., T. Perez, and S. Simison, The influence of microstructure and chemical composition of carbon and low alloy steels in CO2 corrosion. A state-of-the-art appraisal. Materials & Design, 2003. 24(8): p. 561-575.\n[12]\tSchmitt, G. and M. Horstemeier. Fundamental aspects of CO2 metal loss corrosion-Part II: Influence of different parameters on CO2 corrosion mechanisms in CORROSION 2006. 2006. NACE International.\n[13]\tDe Waard, C. and D. Milliams, Carbonic acid corrosion of steel. Corrosion, 1975. 31(5): p. 177-181.\n[14]\tNesic, S., et al. Electrochemical properties of iron dissolution in the presence of CO2-basics revisited in CORROSION 96. 1996. NACE International.\n[15]\tNe\u0161i\u0107, S., Key issues related to modelling of internal corrosion of oil and gas pipelines\u2013A review. Corrosion Science, 2007. 49(12): p. 4308-4338.\n[16]\tFang, H., B. Brown, and S. Ne\u0161ic, Sodium chloride concentration effects on general CO2 corrosion mechanisms. Corrosion, 2013. 69(3): p. 297-302.\n[17]\tMishra, B., et al., Development of a predictive model for activation-controlled corrosion of steel in solutions containing carbon dioxide. Corrosion, 1997. 53(11): p. 852-859.\n[18]\tNesic, S., J. Postlethwaite, and S. Olsen, An electrochemical model for prediction of corrosion of mild steel in aqueous carbon dioxide solutions. Corrosion, 1996. 52(4): p. 280-294.\n[19]\tNordsveen, M., et al., A mechanistic model for carbon dioxide corrosion of mild steel in the presence of protective iron carbonate films-Part 1: Theory and verification. Corrosion, 2003. 59(5): p. 443-456.\n[20]\tOgundele, G. and W. White, Some observations on corrosion of carbon steel in aqueous environments containing carbon dioxide. Corrosion, 1986. 42(2): p. 71-78.\n[21]\tDavid, E., C. Robert, and G. Rosa, Effect of microalloying, principally with vanadium, processing conditions and microstructure on resistance to CO2 corrosion. Journal of Iron and Steel Research (International), 2011. 1.\n[22]\tE-112, A., Standard test methods for determining average grain size. 2010, ASTM International USA.\n[23]\tLopez, D.A., S. Simison, and S. De Sanchez, The influence of steel microstructure on CO2 corrosion. EIS studies on the inhibition efficiency of benzimidazole. Electrochimica Acta, 2003. 48(7): p. 845-854.\n[24]\tOchoa, N., et al., CO2 corrosion resistance of carbon steel in relation with microstructure changes. Materials Chemistry and Physics, 2015. 156: p. 198-205.\n[25]\tAl-Hassan, S., et al., Effect of microstructure on corrosion of steels in aqueous solutions containing carbon dioxide. Corrosion, 1998. 54(6): p. 480-491.\n[26]\tZhao, Y., et al., The mechanical properties and corrosion behaviors of ultra-low carbon microalloying steel. Materials Science and Engineering: A, 2007. 454: p. 695-700.\n[27]\tVera, R., F. Vinciguerra, and M. Bagnara, Comparative study of the behavior of API 5L-X65 grade steel and ASTM A53-B grade steel against corrosion in seawater. Int. J. Electrochem. Sci, 2015. 10: p. 6187-6198.\n[28]\tMorrison, W. Overview of microalloying in steel. in The proceedings of the vanitec symposium, Guilin, China. 2000.\n[29]\tMatlock, D. and J. Speer, Microalloying concepts and application in long products. Materials Science and Technology, 2009. 25(9): p. 1118-1125.\n[30]\tPalacios, C. and J. Shadley, Characteristics of corrosion scales on steels in a CO2-saturated NaCl brine. Corrosion, 1991. 47(2): p. 122-127.\n[31]\tTanupabrungsun, T., B. Brown, and S. Nesic. Effect of pH on CO2 Corrosion of Mild Steel at Elevated Temperatures. in Corrosion/2013 NACE International Conference & Expo. Ohio University. 2013.\n[32]\tDugstad, A., H. Hemmer, and M. Seiersten. Effect of steel microstructure upon corrosion rate and protective iron carbonate film formation. in CORROSION 2000. 2000. NACE International.\n[33]\tSeikh, A.H., Influence of Heat Treatment on the Corrosion of Microalloyed Steel in Sodium Chloride Solution. Journal of Chemistry, 2013. 2013.\n[34]\tG102-89, A., Standard practice for calculation of corrosion rates and related information from electrochemical measurements. 1999, ASTM International West Conshohocken, Pa.\n[35]\tTait, W.S., An introduction to electrochemical corrosion testing for practicing engineers and scientists. 1994: Clair, Racine, Wis."]}